2022
DOI: 10.3389/feart.2022.852485
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Distribution of Water and Salt Elements in Arid Irrigation Areas and Soil Salination Evolution

Abstract: Long periods of surface water irrigation and water and salt movement have slow and continuous influence on the evolution of soil salinization in a closed hydrogeological unit of arid irrigation areas. It is of more application value to study the evolution process of soil salinization from the perspective of regional medium and long terms in the regional scale for the sustainable development of irrigated areas. In this study, the spatial–temporal evolution of soil salinization and dominant factors for soil sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Few studies have evaluated the influence of groundwater table depth change on soil salinization degree on long‐term scales. Lian et al (2022) showed that the long‐term evolution of groundwater table depth has a slow impact on the development of regional soil salinization and that there is a logarithmic relationship between the growth rate of soil salt content and groundwater table depth. How changes in groundwater table depth affect soil salinization on longer time scales is unclear and needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the influence of groundwater table depth change on soil salinization degree on long‐term scales. Lian et al (2022) showed that the long‐term evolution of groundwater table depth has a slow impact on the development of regional soil salinization and that there is a logarithmic relationship between the growth rate of soil salt content and groundwater table depth. How changes in groundwater table depth affect soil salinization on longer time scales is unclear and needs further study.…”
Section: Introductionmentioning
confidence: 99%